2019
DOI: 10.21203/rs.2.9987/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Larva of greater wax moth Galleria mellonella is a suitable alternative host for the fish pathogen Francisella noatunensis subsp. orientalis

Abstract: Background Francisella noatunensis subsp. orientalis (Fno) is the etiological agent of francisellosis in cultured warm water fish, such as tilapia. Antibiotics are administered to treat the disease but a better understanding of Fno infection biology will inform improved treatment and prevention measures. However, studies with native hosts are costly and considerable benefits would derive from access to a practical alternative host. Here, larvae of Galleria mellonella were assessed for suitability to study Fno… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Based on RNAi phenotypes, the same section of ventral abdominal integument (the seventh body segment) was dissected from each sample. All samples were fixed in 4% paraformaldehyde at 4°C for at least 2 days to prepare paraffin sections, and stained with hematoxylin and eosin in accordance with the protocol described by Djainal et al 32 . The slides were observed under an OLYMPUS BX51 microscope (Olympus), and photographs were taken using an OLYMPUS digital camera.…”
Section: Methodsmentioning
confidence: 99%
“…Based on RNAi phenotypes, the same section of ventral abdominal integument (the seventh body segment) was dissected from each sample. All samples were fixed in 4% paraformaldehyde at 4°C for at least 2 days to prepare paraffin sections, and stained with hematoxylin and eosin in accordance with the protocol described by Djainal et al 32 . The slides were observed under an OLYMPUS BX51 microscope (Olympus), and photographs were taken using an OLYMPUS digital camera.…”
Section: Methodsmentioning
confidence: 99%
“…We estimated the virulence of our S. marcescens strains by measuring the longevity of waxmoth larvae ( Galleria mellonella ) injected with 5 μl of bacterial culture. G. mellonella is a good model for bacterial virulence as it has been shown that virulence in this host is also a good proxy for virulence in vertebrate hosts such as mouse or fish (Djainal et al, 2020; Jander et al, 2000). We grew bacterial cultures of evolved strains overnight at 31°C in Bioscreen wells in 400 μl of SPL 1% inoculated with the strains frozen stocks using a cryoreplicator.…”
Section: Methodsmentioning
confidence: 99%
“…We estimated the virulence of our S. marcescens strains by measuring the longevity of waxmoth larvae ( Galleria mellonella ) injected with 5 μl of bacterial culture. G. mellonella is an interesting model for bacterial virulence as it had been shown that virulence in this host is also a good proxy for virulence in vertebrate hosts such as mouse or fish (Jander et al, 2000; Djainal et al, 2020). We grew bacterial cultures of evolved strains overnight at 31 °C in Bioscreen wells in 400 μl of SPL 1 % inoculated with the strains frozen stocks using a cryoreplicator.…”
Section: Methodsmentioning
confidence: 99%